MEDIA ONLINE “MOGIGU” EFFECTIVE FOR INCREASING KNOWLEDGE ABOUT TOOTHBRUSHING ON ELEMENTARY SCHOOL STUDENTS GROBOGAN REGENCY - Joni Satria; Diyah Fatmasari (Poltekkes Kemenkes Semarang, 2020)
Dental caries is a dental health problem that is widely found in Indonesia. One way to improve a child's knowledge of maintaining dental and oral health is to provide dental health education on how to brush the teeth properly using appropriate and innovative tools or media. The type of research is quasi-experiment with pretest and posttest group design, sampling technique using Slovin formula. Media to increase knowledge is media online